KNOWLEDGE TO PRACTISE: USING SERVQUAL THEORY TO EXAMINE STUDENTS’ INTENTION TO PRACTISE CULINARY SKILL DURING ONLINE DISTANCE LEARNING - Nor Hafizah Mazlan; Siti Aisyah Tumin; Suria Sulaiman; Anderson Ngelambong; Amirul Hakim Zulkifi (Journal of Islamic, Social, Economics and Development, 2023)
Online distance learning has become the norm in higher-learning education due to the Covid-19 pandemic. There is a dearth of research that investigates the effectiveness of online based learning used to deliver practical courses such as culinary cooking classes. Culinary cooking courses are unique from theory-based courses as they require hands-on demonstration of cooking knowledge, skill and practice. This study aims to examine the factors that influence students’ intention to practice their culinary skill at home from a service quality (SERVQUAL) theoretical lens. The target population is undergraduate students who have experience in ODL practical-based culinary courses. Two UiTM campuses that offer Culinary Arts programmes were chosen from Pulau Pinang and Dungun. An online survey was distributed to 300 respondents and 181 questionnaires were received. Correlation analysis was carried out to find out the direction and strength of the relationship between the Online Service Quality variables namely responsiveness, empathy, assurance, reliability, content delivery, facilitation of interaction and perceived behavioural control towards behavioural intention of the students. Results of Pearson correlation coefficients (p value) range from 0.375 to 0.640. These findings contribute to a better understanding on how SERQUAL attributes are important to enhance students’ intention to practice culinary skill at home. Also provides essential information in assessing and improving the learning experience which would contribute knowledge for instructor, organization and also Ministry of Education in enhancing MOOC and learning environment.